A Mathematical Framework for Modeling the Spread of HIV-disease within two Different Age Classes (European Journal of Pure and Applied Mathematics, 2023)
In this paper, we propose a mathematical model for the spread of HIV disease within two different age classes. We define a basic reproduction number R0 that depends on the characteristics of the two age classes. We prove that if R0 less than 1, then the disease is extinct in both age classes. In contrast, we prove that if R0 greater than 1, then the disease is endemic in both age classes.
Keywords: HIV-AIDS; epidemic model; basic reproduction number; asymptotic stability; global stability; numerical simulations